1996
DOI: 10.1177/08959374960100020201
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure of the Porcine 89-kDa Enamelin

Abstract: The primary structure of the 89-kDa enamelin found in porcine secretory enamel at an early stage of development was investigated. The fragments of the enamelin cDNA were amplified by polymerase chain-reaction from the first-strand enamelin cDNA, and were sequenced. The results indicated that the 89-kDa enamelin consisted of 627 amino acid residues and had a molecular mass of 70,448. A hydrophobic domain is located in the region of the 21st-62nd amino acid residues of the molecule. Acidic domains are located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
97
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 14 publications
5
97
1
1
Order By: Relevance
“…Pig enamelin is secreted as a 186-kDa (1104 amino acids) glycoprotein that is rapidly processed, probably by MMP-20, in the extracellular space (21). The secreted protein is processed from its C terminus to generate 155-, 145-, and 89-kDa (Met 1 -Trp 627 ) N-terminal cleavage products, but these cleavage products do not last long and are found only near the enamel surface (41,62). Secretion, proteolytic processing, and reabsorption of selected cleavage products back into ameloblasts determine the makeup of the organic matrix that controls mineralization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pig enamelin is secreted as a 186-kDa (1104 amino acids) glycoprotein that is rapidly processed, probably by MMP-20, in the extracellular space (21). The secreted protein is processed from its C terminus to generate 155-, 145-, and 89-kDa (Met 1 -Trp 627 ) N-terminal cleavage products, but these cleavage products do not last long and are found only near the enamel surface (41,62). Secretion, proteolytic processing, and reabsorption of selected cleavage products back into ameloblasts determine the makeup of the organic matrix that controls mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…These enamel proteins have multiple glycosylation sites and other post-translational modifications, even hydroxyproline (41,42), and efforts to generate recombinant forms with the appropriate modifications have failed to produce them in any significant quantity (43). Therefore, it is currently impossible to reconstitute the secretory stage extracellular matrix and recapitulate the formation of enamel crystals in vitro.…”
Section: Correct Targeting Of the Transgene Was Confirmed By Southementioning
confidence: 99%
“…The SDS-PAGE electrophoretic profile of whole enamel homogenates from immature enamel is very complex and represents a composite image of both newly secreted and partially degraded forms from both categories of proteins (reviewed in Smith and Nanci 1996). Enamelin, ameloblastin (also known as sheathlin and amelin), and tuftelin are the best-known members of the nonamelogenin family (Deutsch et al 1991(Deutsch et al ,1995bCerny et al 1996;Fukae et al 1996;Krebsbach et al 1996;Hu et al 1997a,b). A glycosylated and sulfated nonamelogenin with molecular weight near 65 kD and major fragmented forms near 50 and 25 kD has also been described in rat enamel Smith and Nanci 1996).…”
mentioning
confidence: 99%
“…For this, one should consider that these cells have a different origin; epithelial to ameloblasts and cells derived from the neural crest to the odontoblasts and that each cell type produces different matrices, respectively enamel and dentin. In studies, using scanning electron microscopy and in situ hybridization was observed that enamelysin is secreted by ameloblasts and odontoblasts within enamel and dentin matrices (Bourd-Boittin et al; Furkae et al, 1996).…”
Section: Discussionmentioning
confidence: 99%